Hypochondriasis as an early manifestation of dementia with Lewy bodies: an autopsied case report. Issue 2 (27th April 2015) - Fujishiro, Hiroshige; Iritani, Shuji; Sekiguchi, Hirotaka; Habuchi, Chikako; Torii, Youta; Matsunaga, Shinji; Ozaki, Norio; Yoshida, Mari; Fujita, Kiyoshi
Abstract: Discrepancies between clinical and pathological diagnoses of dementia with Lewy bodies (DLB) may occur because the full disease progression remains unclear, especially during the early stage. Herein, we report the case of a 78‐year‐old Japanese man with hypochondriasis who had autopsy‐confirmed limbic‐type DLB pathology. He exhibited no core clinical features of DLB. We attempted to identify the clinicopathological correlations in the early stages of DLB. At the age of 77, he became hypochondriacal and exhibited progressive cognitive decline after the death of his wife. He was concerned about his poor physical condition, but hospital examinations did not identify any overtly abnormal findings. At 78 years of age, he consulted a neurologist with complaints of facial numbness and irritability . Neurological examination revealed no overt abnormality, and he scored 21 points on the Mini‐Mental State Examination. Magnetic resonance imaging of the brain showed mild bilateral ventricular enlargement. The patient was clinically diagnosed as having possible Alzheimer's disease. Approximately 1 month after his consult, he died of acute pneumonia in a psychiatric hospital to which he had been admitted for severe aggressive behaviour. He exhibited no core clinical features pointing towards a clinical diagnosis of DLB. Neuropathological investigation revealed limbic‐type Lewy body disease with concurrent minimum Alzheimer‐type pathology, which corresponds to high‐likelihood DLB pathology based on the Third Consortium DLB pathological criteria. The patient had minimum nigral degeneration, which is consistent with the absence of parkinsonism. This autopsied case suggests that some DLB patients exhibit hypochondriasis in the early stage of the disease, even if they lack the core clinical features of DLB.